Patient and public involvement and engagement in the ASCEND PLUS trial: reflections from the design of a streamlined and decentralised clinical trial - El-Nayir, M; Wijesurendra, R; Preiss, D; Mafham, M; Tsiotos, L; Islam, S; Whitehouse, A; Wilkinson, S; Freeman, H; Lee, R; Brudlo, W; Bobby, G; et al. (BioMed Central, 2024)
Introduction ASCEND PLUS is a randomised controlled trial assessing the effects of oral semaglutide on the primary prevention of cardiovascular events in around 20,000 individuals with type 2 diabetes in the UK. The trial’s innovative design includes a decentralised direct-to-participant invitation, recruitment, and follow-up model, relying on self-completion of online forms or telephone or video calls with research nurses, with no physical sites. Extensive patient and public involvement and engagement (PPIE) was essential to the design and conduct of ASCEND PLUS.